2017
DOI: 10.1371/journal.pntd.0005382
|View full text |Cite
|
Sign up to set email alerts
|

Killing of diverse eye pathogens (Acanthamoeba spp., Fusarium solani, and Chlamydia trachomatis) with alcohols

Abstract: BackgroundBlindness is caused by eye pathogens that include a free-living protist (Acanthamoeba castellanii, A. byersi, and/or other Acanthamoeba spp.), a fungus (Fusarium solani), and a bacterium (Chlamydia trachomatis). Hand-eye contact is likely a contributor to the spread of these pathogens, and so hand washing with soap and water or alcohol–based hand sanitizers (when water is not available) might reduce their transmission. Recently we showed that ethanol and isopropanol in concentrations present in hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Because water for washing hands may be scarce in places where the free-living protist is frequent, we recently showed that alcohols in concentrations present in hand sanitizers kill A . castellanii trophozoites and cysts [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Because water for washing hands may be scarce in places where the free-living protist is frequent, we recently showed that alcohols in concentrations present in hand sanitizers kill A . castellanii trophozoites and cysts [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“… 15 Furthermore, ethanol has been found to have a cytotoxic effect on some infectious forms of Acanthamoeba . 16 , 17 Therefore, soaking the cornea for 30 seconds in ethanol before debridement not only allows ophthalmologists to easily separate the full thickness of the epithelial layer from the basement membrane in both young and older patients with AK, but also had some parasiticidal effects. Moreover, the larger specimens harvested during debridement ensure not only a higher chance of diagnosing AK but also a better chance of penetration of topical anti-amoebic agents.…”
Section: Discussionmentioning
confidence: 99%
“…A. castellanii Neff strain trophozoites were purchased from the American Type Culture collection. Trophozoites of A. castellanii MEEI 0184 strain, which was derived from a human corneal infection, were obtained from Dr. Noorjahan Panjwani of Tufts University School of Medicine (9). Trophozoites were grown in T-75 tissue culture flasks at 30°C in 10 ml ATCC medium 712 (PYG plus additives) (Sigma-Aldrich Corporation, St. Louis, MO) (11).…”
Section: Methodsmentioning
confidence: 99%
“…Acanthamoeba is an emerging pathogen, because 80 to 90% of infections are associated with contact lens use, which is growing worldwide (6, 7). Because water for washing hands may be scarce in places where the free-living protist is frequent, we recently showed that alcohols in concentrations present in hand sanitizers kill A. castellanii trophozoites and cysts (8, 9).…”
Section: Introductionmentioning
confidence: 99%